The Asthma-associated PER1-like domain-containing protein 1 (PERLD1) Haplotype Influences Soluble Glycosylphosphatidylinositol Anchor Protein (sGPI-AP) Levels in Serum and Immune Cell Proliferation - Sio, Yang Yie (Sci Rep, 2020)
Post-glycosylphosphatidylinositol (GPI) attachment to proteins 3, also known as PGAP3 or PERLD1 (PER1-like domain-containing protein 1), participates in the lipid remodeling process of glycosylphosphatidylinositol (GPI) anchor proteins during post-translational modification. Functional defect in PERLD1 was previously hypothesized to influence this process in T-cells and their subsequent activation and proliferation. This current study aims to functionally characterize PERLD1 genetic variants and relate this with human immune cells proliferation rate upon stimulation. We first showed the association between a PERLD1 tag-single nucleotide polymorphism (tagSNP), rs2941504, and the development of asthma in our study population. This association remained significant after conditioning for the other asthma-associated SNP rs8076131 that is also located within the 17q12–21 region. Subsequent sequencing of 40 unrelated Singapore Chinese individuals identified 12 more common PERLD1 SNPs (minor allele frequency > 5%) that are in linkage disequilibrium (LD, r(2) > 0.8) with rs2941504. Through in vitro studies, 7 of these SNPs were found to form a functional haplotype that influences alternative splicing of PERLD1 transcript. This result was validated in human peripheral blood mononuclear cell (PBMC), where the minor haplotype (Hap2) was shown to be associated with significantly increased PERLD1 truncated transcript. Additionally, Hap2 was found to be related to increased levels of several soluble GPI-anchored proteins (such as sCD55 and sCD59) in serum. Elevated sCD55 in the serum was demonstrated to reduce the proliferation rate of PBMCs upon phytohaemagglutinin (PHA) stimulation. Taken together, the current study has shown a functional PERLD1 haplotype, which modifies PBMC sensitivity upon stimulation and may contribute to the individual’s susceptibility to allergic asthma.